1996
DOI: 10.1161/01.cir.94.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Routine Coronary Angiography After Acute Myocardial Infarction

Abstract: In many patient subgroups after AMI, the cost-effectiveness of routine coronary angiography and treatment guided by its results compares favorably with other treatment strategies for coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Our findings are also in general agreement with the cost-effectiveness model of Kuntz et al, 21 who found that coronary angiography was highly cost-effective in patients with postinfarction angina and a strongly positive exercise test, criteria for angiography similar to those of our conservative, ischemia-guided management strategy. By contrast, their model found that angiography was not cost-effective in the absence of postinfarction angina or a positive exercise test.…”
Section: Cost-effectivenesssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are also in general agreement with the cost-effectiveness model of Kuntz et al, 21 who found that coronary angiography was highly cost-effective in patients with postinfarction angina and a strongly positive exercise test, criteria for angiography similar to those of our conservative, ischemia-guided management strategy. By contrast, their model found that angiography was not cost-effective in the absence of postinfarction angina or a positive exercise test.…”
Section: Cost-effectivenesssupporting
confidence: 91%
“…By contrast, their model found that angiography was not cost-effective in the absence of postinfarction angina or a positive exercise test. 21 Although different in design, the model of Kuntz et al 21 agrees with our finding that a selective approach to coronary angiography after myocardial infarction is more cost-effective.…”
Section: Cost-effectivenesssupporting
confidence: 77%
“…Laupacis et al 16 suggested that interventions with an icer of less than $20,000/qaly are cost-effective and those with an icer of more than $100,000/qaly are not costeffective; however, those figures are based on 1992 dollars. A few influential and widely cited articles use $50,000/qaly as the threshold 17,18 . In a recent survey of oncologists in both Canada and the United States, 49%-56% of respondents thought that a reasonable cost-effectiveness ratio was $50,000 to $100,000 per 30,604 --icer = incremental cost-effectiveness ratio; gem = gemcitabine; cap = capecitabine; e = erlotinib; folfirinox = 5-fluorouracil-leucovorinirinotecan-oxaliplatin; qalys = quality-adjusted life years.…”
Section: Discussionmentioning
confidence: 99%
“…Kuntz et al (39), using a decision analysis, assessed the cost-effectiveness of coronary angiography to identify candidates for revascularization after acute myocardial infarction (AMI). Data on effectiveness were based on randomized trials comparing CABG with medical therapy, since there had been no completed trials involving PTCA at the time.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…The number of LYs was the metric of health outcome used in all the primary and secondary prevention CEAs (17,24,29,66). The analyses of tertiary prevention measures were more likely to use QALYs (29,39,45). Quality weights were likely to be based on physician or patient (rather than community) preferences (77).…”
Section: Coronary Heart Diseasementioning
confidence: 99%